Pariwisata Budaya dan Pandemi Covid-19: Memahami Kebijakan Pemerintah dan Reaksi Masyarakat Bali - I Nengah Subadra (Pusat Kajian Bali Universitas Udayana, 2021)
The research is aimed at understanding the government policies on cultural tourism and pandemic mitigations in Bali made during the covid-19 pandemic. It uses qualitative method in which the primary data were collected through face-to-face and virtual video interviews to seven informants who were selected using purposive sampling to assure they aware of and understand the researched case; and the secondary data were collected from online publications. The research finds the regional regulation on cultural tourism was amended during the Covid-19 outbreak to strengthen the use of local cultures for tourism adapting both national and international tourism policies to lead to a more responsible tourism designating Bali’s local indigenous cultures of Tri Hita Karana and Sad Kerthi as basis of cultural tourism development in Bali; and more importantly, Bali’s government issued particular policies and executed immediate measures to reopen tourism in Bali which totally shut down due to pandemic. These policies reacted differently by local people and remains become a hot debate within Balinese communities.